Pengaruh Event-Based Marketing, Sensory Marketing, Dan User Generated Content Terhadap Loyalitas Merek Jiniso (Studi Pada Pada Mahasiswa Unisma) - Oktaviani Laili Rakhmawati; Rois Arifin; Alfian Budi Primanto (UNIVERSITAS ISLAM MALANG, 2026)
Abstract This study aims to analyze the influence of Event-Based Marketing, Sensory Marketing, and User-Generated Content (UGC) on Jiniso Jeans brand loyalty among students at the Universitas Islam Malang. This study used a quantitative approach with a survey method by distributing questionnaires to 110 respondents selected using a purposive sampling technique. The data analysis technique used was multiple linear regression analysis with the help of SPSS. The results showed that simultaneously, Event-Based Marketing, Sensory Marketing, and User-Generated Content significantly influenced Brand Loyalty. Partially, Event-Based Marketing and Sensory Marketing significantly influenced Brand Loyalty, while User-Generated Content did not. These results indicate that in the context of marketing through TikTok Shop, consumer loyalty is more influenced by event experiences and sensory stimuli than by user-generated content. This research is expected to serve as a reference for companies in designing more effective digital marketing strategies to increase brand loyalty. Keywords: Event-Based Marketing, Sensory Marketing, User-Generated Content, Brand Loyalty